2018
DOI: 10.18632/oncotarget.24058
|View full text |Cite
|
Sign up to set email alerts
|

Cyclictrans-phosphorylation in a homodimer as the predominant mechanism of EGFRvIII action and regulation

Abstract: Despite intensive research no therapies targeted against the oncogenic EGFRvIII are present in the clinic. One of the reasons is the elusive nature of the molecular structure and activity of the truncated receptor. The recent publications indicate the EGF-bound wild-type EGFR to trans-phosphorylate the EGFRvIII initiating aberrant signaling cascade. The elevated stability of the mutant receptor contributes towards oncogenic potential, preventing termination of signaling by receptor degradation. Here, we show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 49 publications
(102 reference statements)
1
10
0
1
Order By: Relevance
“…Importantly, it has to be emphasized that EGFR vIII exhibits constitutive activity [121,122]. Our team demonstrated that mutant phosphorylation is elevated when compared to nonstimulated EGFR WT , while data obtained by other research teams indicate that constitutive EGFR vIII signaling corresponds to low level of signal intensity induced by ligand-activated EGFR WT [17,[123][124][125]. Such data indicate that EGFR vIII dimer conformation resembles inactive dimers of EGFR WT , thus suggesting that impact of this oncogenic receptor on cell biology is not a result of some specific, dimerization-related kinase activity, but rather a consequence of unique membrane stability [121,122].…”
Section: Egfr VIII Mechanism Of Actionmentioning
confidence: 66%
See 4 more Smart Citations
“…Importantly, it has to be emphasized that EGFR vIII exhibits constitutive activity [121,122]. Our team demonstrated that mutant phosphorylation is elevated when compared to nonstimulated EGFR WT , while data obtained by other research teams indicate that constitutive EGFR vIII signaling corresponds to low level of signal intensity induced by ligand-activated EGFR WT [17,[123][124][125]. Such data indicate that EGFR vIII dimer conformation resembles inactive dimers of EGFR WT , thus suggesting that impact of this oncogenic receptor on cell biology is not a result of some specific, dimerization-related kinase activity, but rather a consequence of unique membrane stability [121,122].…”
Section: Egfr VIII Mechanism Of Actionmentioning
confidence: 66%
“…Additionally, our data indicate that EGFR vIII signaling may not be associated with slightly elevated kinase activity, but rather its minimally lower sensitivity to phosphatase activity, when compared to wild-type receptor [123]. Moreover, we indicated that enhanced phosphorylation of tyrosine 1045 did not result in EGFR vIII degradation [123], suggesting that the previous model of impaired EGFR vIII degradation requires an update [121]. Nevertheless, without membrane stability, EGFR vIII signaling will not be strong enough to induce a biological effect.…”
Section: Egfr VIII Mechanism Of Actionmentioning
confidence: 69%
See 3 more Smart Citations